RELIABILITY AND VALIDITY OF KNOWLEDGE AND BEHAVIOURS RELATED FOOD ADDITIVES SCALE - Erci, Behice; ErÄ±ÅŸÄ±k, Ela (Advances in Nursing & Midwifery, 2018)
Background: Food additive is an important reason for health risk. The hazards that most people were concerned about in relation to food additives were the risks of developing allergy, cancer and disturbing the hormone balance. Objective: The objective of this study was to develop and assess the validity and the reliability of the knowledge and behaviours related food additives scale. Methods: The population for this study consisted of mothers with 1- to 12- year-old children in Ağrı, Turkey. A convenience sample was recruited from the mothers attending two primary health care centres in the town. The sample size was determined to be 413 mothers by conducting power analysis. Data were collected using questionnaire including demographic characteristics and the knowledge and behaviours related food additives scale. The researchers visited the primary healthcare centre and conducted interviews with the mothers. The questionnaire took 15-20 min to complete and could be understood by people with minimal reading ability. Results: Factor analysis revealed two factors were the behaviour related food additives subscale and the knowledge related food additives subscale. The two factors together explained 53.7% of the variance. Internal consistency reliability of the whole questionnaire was 0.74. Conclusion and Recommendation: The knowledge and behaviours related food additives scale is very important because it provides standardized data mother’s attitude knowledge and behaviour regarding a child’s health for food additives.